Absence of the Musculocutaneous Nerve; Two Case Reports and Literature Review - Abdelmotalab, Mohammed (AL-Kindy College Medical Journal, 2024)
The musculocutaneous nerve is important in the upper extremity because it provides motor innervation to the musculature of the anterior arm region and sensory innervation to the skin on the lateral side of the forearm region. During the dissection of approximately 74 aged male cadaver for the 2021-2022 academic year at the Department of Anatomy, Faculty of Medicine, International University of Africa, Sudan. Considerable variation was present; the musculocutaneous nerve was observed to be absent in both upper extremities. The median nerve replaces the musculocutaneous nerve innervation’s role on both sides except for the coracobrachialis muscle on the right side. A direct branch from the lateral cord innervated it. Reporting these variations has a critical impact on many surgical and clinical procedures.